14th Congress of the Mediterranean Phytopathological Union and International Society of Mycotoxicology (Mediterranean Branch), Istanbul, Turkey, 25–29 August 2014 - , (Phytopathologia Mediterranea, 2015)
The joint 14th Congress of Mediterranean Phytopathological Union and International Society of Mycotoxicology (Mediterranean Branch) was held in Istanbul, Turkey, on August 25–29 2014. The invited lectures, oral and poster presentations covered aspects of plant diseases caused by fungi, bacteria, viruses, protozoa and non-parasitic disorders, and with disease control. Particular attention was given to the Congress theme “Plant health management for ensuring food security, safety and quality in the Mediterranean area: Challenges and prospects”. In addition, round-table discussions was held on “Xylella fastidiosa: a serious menace to the Mediterranean fruit industry” (chaired by Anna Maria D’Onghia, Italy), and “Epidemiology and control of new spreading virus diseases of economic importance in the Mediterranea basin” (chaired by Khaled Makkouk, Lebanon). Abstracts of the invited papers, and of the offered oral and posters presentations are given in this issue.